Financial instruments for ensuring national security: experience of Ukraine in military conditions - Oksana Radchenko; Leonid Tulush; Serhii Leontovych (Insights into Regional Development)
State security is the main guideline of state policy in the face of global challenges. For Ukraine, it is especially relevant, because during the period of the russian-Ukrainian war, its foundations and essence experience significant deformations. Since the risks and threats to national security have increased enormously in Ukraine under martial law, its financial component should be formed according to the tools corresponding to the challenges, even ahead of them, since, according to analysts, modern war is a war of finances. The problems faced by the state, the banking system, financial and commodity markets and institutions, corporations and households need new financial instruments to ensure flexibility in financing strategic goals. As of September, the losses of the Ukrainian economy from the war are estimated according to various estimates, from USD 105 billion, or 70% of the average annual GDP over the past 5 years, to USD 600 billion, and this exceeds the level of GDP in 2021 by 3 times. This actualizes the needs of the scientific study of financial instruments with the aim of effective state regulation and equalization in the face of limited and increasing losses of human and material resources, changes in the direction and speed of financial flows, their sources, structure, reproduction and reservation. The study examines financial instruments of a predominantly budgetary direction, as well as the components of national indicators of financial security. It is also important to analyze the share of the state in the economy, the size of which determines the speed of response and the completeness of resistance due to a threat to national security. To achieve the goals of the study, the main legally established risks of financial instruments of the national economy during the period of martial law are systematized. The indicators of the financial security of the state for the period of hybrid and military aggression of the rf (2013-2021) were assessed, and according to open sources of data, which are rather limited, a forecast of these indicators for 2022 was made. On the basis of the Financial Stability Report of the National Bank of Ukraine, the budget innovations of the period of martial law are analyzed. The sources of financing the state budget for the period of the legal regime of martial law and its main directions for 2023 are summarized. It is concluded that the financial system of Ukraine in a short time managed to organize financial flows in accordance with the needs of ensuring national security, form an optimal balance of resources, maintain the volume of financing of basic budget expenditures, attract donor resources and resist the inevitable decline of the economy during the war. The role of donor countries of economic and military assistance, in particular Latvia, in deterring military aggression and ensuring the stability of Ukraine's financial policy was emphasized.